Implementation of an information hiding scheme at physical layer of wireless communications - Aw, Benjamin Wei Lin (2018)
Security in wireless communication is a key concern. At times when secretive or confidential information needs to be transmitted through wireless communication systems, information hiding schemes are employed. In this report, an innovative information hiding scheme capable of embedding secret at the physical layer of a wireless communication system without impact on its original performance is introduced. Variable pulse shaping is used in said scheme to embed secret bits in the data to be transmitted. Unlike existing hiding schemes, the variable pulse shaping scheme is noiseless, stealthy, transparent and robust. The main objective was to implement the variable pulse shaping scheme onto a reference wireless communication system in hardware form. Simulations performed on the hardware realization tells us that the proposed scheme operates as intended even at radio frequencies. This study benefits the field by providing a new method of embedding secret information which is suitable in many applications such as authentication and message watermarking.